DAMPAK KEPEMIMPINAN, STRES DAN SIKAP KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL - Heru Sri Wulan (Universitas Pandanaran, 2019)
One measurement of the employee performance of Manpower, Transmigration and Population Service of Central Java Provincial Government is the number of transmigrantsdeparture.Theresultsofevaluationofthenumberofmigrantsandthenumberofmigrantswho departed show that the realization had not reach 100% and the trend ofdeclining. Based on these empirical phenomena, the statement expressing the problem isthe employee performance of Manpower, Transmigration and Population Service ofCentral Java Provincial Government had not meet the target and tend to decrease.Therefore this study aimed to investigate the effect of job stress and attitudes onperformance in order to improve the employee performance Manpower, Transmigrationand Population Service of Central Java Provincial Government. To answer these research purposes, interviewing with 98 respondents wereconducted using questionnaire to obtain data/information on job stress, attitudes, andperformance. The respondents are the employees of Manpower, Transmigration andPopulation Service of Central Java Provincial Government. The data obtained wasanalyzed using multiple regression tests. The results of multiple regression tests on the variables of job stress, work attitudes,and performance showed that job stress is proven to have significant and negative effecton the employee performance of Manpower, Transmigration and Population Service ofCentral Java Provincial Government and work attitude is proven to have significant andnegative effect on the employee performance of Manpower, Transmigration andPopulation Service of Central Java Provincial Government.Keywords: job, stress, work attitude, performance